2016
DOI: 10.11646/zootaxa.4154.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of two endemic Indian skinks, Eutropis bibronii (Gray, 1838)<br />and E. nagarjunensis (Sharma, 1969) (Reptilia: Scincidae), including redescriptions of their types

Abstract: Tiliqua bibronii was described by J.E. Gray in December, 1838 based on two syntypes (MNHN-RA 2940, 7076), but the details for locality was missing. These syntypes are currently housed at the Muséum national d'Histoire naturelle, Paris, France (MNHN-RA). The same species (based on the same type specimens) was described by A.M.C. Duméril & G. Bibron in November, 1839 nearly one year after Gray's publication. As such, Gray's publication must therefore be given priority. Another species, Euprepis trilineatus, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 553 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Mature males were observed in late December were with red throat and sides of neck. Remarks: This species was recently redescribed (Amarasinghe et al, 2016b).…”
Section: Nagarjunsagar Skink Eutropis Nagarjunensis (Sharma 1976)mentioning
confidence: 99%
“…Mature males were observed in late December were with red throat and sides of neck. Remarks: This species was recently redescribed (Amarasinghe et al, 2016b).…”
Section: Nagarjunsagar Skink Eutropis Nagarjunensis (Sharma 1976)mentioning
confidence: 99%
“…It comprises three recognized sub‐families–Acontinae, Scincinae and Lygosominae (Greer, 1970; Pyron, Burbrink, & Wiens, 2013; Shea, 2021; Skinner et al., 2013; Zheng & Wiens, 2016; but see Hedges & Conn, 2012; Hedges, 2014 for an alternate hypothesis), with the subfamily Lygosominae being the most species‐rich (Freitas et al., 2019; Uetz et al., 2023). Two genera of Lygosomines, Eutropis Fitzinger, 1843, and Riopa Gray, 1846, occur both in peninsular India and Sri Lanka, with their other congenerics distributed in Southeast Asia (Amarasinghe et al., 2016; Bauer, 2003). Earlier studies have shown that these two genera have dispersed into the Indian subcontinent from Southeast Asia (Datta‐Roy et al., 2012; Datta‐Roy et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Material: SACON/VR-35a one from Sriharikota, SACON/VR-35b-d three from Tuticorin, SACON/VR-35e-h four from Pondicherry. Comments: This species has recently been redescribed(Amarasinghe et al 2016b). Chandramouli et al (2012) reported an inland record from Eastern Ghats and its status is under investigation.…”
mentioning
confidence: 99%